2010
DOI: 10.1111/j.1365-2648.2009.05181.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dental hygiene education for nursing home staff

Abstract: Dental hygiene education for nursing home staff is important to maintain an adequate level of oral hygiene among older nursing home residents over time. Follow-up of dental hygiene education for nursing home staff is recommended to maintain a sufficient level of oral hygiene among the residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…However, several studies that investigated the effect of an oral health education program for the caretakers did not observe a significant improvement in the oral health status of the elderly residents (Gammack and Pulisetty, 2009;MacEntee et al, 2007;Simons et al, 2000) whereas other studies did observe an improvement (Boczko et al, 2009;Frenkel et al, 2001;Isaksson et al, 2000;Kullberg et al, 2009;Nicol et al, 2005;Portella et al, 2013). Sjogren et al (2010) indicated that a single oral health education of the caregivers yearly was insufficient to improve the oral health status of the residents after 1.5 yrs. Possible reasons for the lack of a significant impact of the caregivers' training on the oral health status of the elderly residents may include relatively good oral health status of residents at baseline (MacEntee et al, 2007), less sensitive measurement scales for the oral health assessments (Gammack and Pulisetty, 2009), too small a sample size to detect a 20% difference (MacEntee et al, 2007), short presentation without adequate training or theory of improved oral health care (Gammack and Pulisetty, 2009), insufficient time due to competing personal care duties (Gammack and Pulisetty, 2009;Reed et al, 2006;Simons et al, 2000), inadequate staffing intensity at facility (Gammack and Pulisetty, 2009;Reed et al, 2006;Simons et al, 2000), insufficient supplies for oral health care (Coleman, 2005), the Hawthorne effect on the facilities and staff (MacEntee et al, 2007), and a relatively high turnover of staff at the facility between the pre and post training assessments (Simons et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, several studies that investigated the effect of an oral health education program for the caretakers did not observe a significant improvement in the oral health status of the elderly residents (Gammack and Pulisetty, 2009;MacEntee et al, 2007;Simons et al, 2000) whereas other studies did observe an improvement (Boczko et al, 2009;Frenkel et al, 2001;Isaksson et al, 2000;Kullberg et al, 2009;Nicol et al, 2005;Portella et al, 2013). Sjogren et al (2010) indicated that a single oral health education of the caregivers yearly was insufficient to improve the oral health status of the residents after 1.5 yrs. Possible reasons for the lack of a significant impact of the caregivers' training on the oral health status of the elderly residents may include relatively good oral health status of residents at baseline (MacEntee et al, 2007), less sensitive measurement scales for the oral health assessments (Gammack and Pulisetty, 2009), too small a sample size to detect a 20% difference (MacEntee et al, 2007), short presentation without adequate training or theory of improved oral health care (Gammack and Pulisetty, 2009), insufficient time due to competing personal care duties (Gammack and Pulisetty, 2009;Reed et al, 2006;Simons et al, 2000), inadequate staffing intensity at facility (Gammack and Pulisetty, 2009;Reed et al, 2006;Simons et al, 2000), insufficient supplies for oral health care (Coleman, 2005), the Hawthorne effect on the facilities and staff (MacEntee et al, 2007), and a relatively high turnover of staff at the facility between the pre and post training assessments (Simons et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
“…1) (Boczko et al, 2009;Frenkel et al, 2001;Isaksson et al, 2000;Nicol et al, 2005;Portella et al, 2013). Four of the twelve excluded studies did not provide quantitative data of the outcome of interest MacEntee et al, 2007;Simons et al, 2000;Sjogren et al, 2010). Four studies (Frenkel et al, 2002;Gammack and Pulisetty, 2009;Khanagar et al, 2014;Reed et al, 2006) did not evaluate the oral health of the elderly.…”
Section: Literature Searchmentioning
confidence: 86%
See 1 more Smart Citation
“…We previously constructed a new dental hygiene educational model for nursing home staff evaluated it for its effect on the dental hygiene of nursing home resident older people, and this work has been reported in detail elsewhere (Kullberg et al 2009, Sjö gren et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…2 The educational model has shown promising results in terms of improved attitudes towards oral hygiene tasks among the staff members, and has sustainably improved the oral hygiene among the residents. 2,3 The dental profession needs to be integrated as a natural part of the current care-chains of older people. This is not only a matter of reducing suffering among older people, but can also lead to a considerable net gain in dental and medical care costs, since preventive dental care is cheaper than restorative care, not to mention the costs of general health complications due to poor oral hygiene.…”
mentioning
confidence: 99%